2004
DOI: 10.1111/j.1601-5223.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Apospory in Bahiagrass, Paspalum Notatum

Abstract: Previous studies on the inheritance of aposporous apomixis in bahiagrass showed a wide range of segregation ratios in crosses involving sexual and aposporous apomictic plants. The F1 progenies were classified through a visual progeny test carried out on few F2 plants. The number of sexual F1s highly exceeded the apomictics leading to the conclusion that apomixis was controlled by a few recessive genes. The present study examines the inheritance of apospory in bahiagrass. A sexual plant was self-pollinated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
91
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 14 publications
5
91
1
2
Order By: Relevance
“…The ratio of 1:2.6 (sexual plants:apomictic) was found; however, in studies conducted at IBONE, evaluating 44 hybrids, Martínez et al (2001) found a ratio of 4.5:1 (sexual:apomictic). This distorted segregation is possibly related to the lethal effect of the dominant pleiotropic locus or partial lethality factors linked to the aposporic gene.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The ratio of 1:2.6 (sexual plants:apomictic) was found; however, in studies conducted at IBONE, evaluating 44 hybrids, Martínez et al (2001) found a ratio of 4.5:1 (sexual:apomictic). This distorted segregation is possibly related to the lethal effect of the dominant pleiotropic locus or partial lethality factors linked to the aposporic gene.…”
Section: Resultsmentioning
confidence: 80%
“…Contrary to that found in this study, Fortes et al (2004) mentioned that this distortion had been found responsible for values of 4.3:1 (sexual:apomictic), differing from the expected 1:1. Martínez et al (2001) found values of 2.8:1 (sexual: apomictic), while the work of Stein et al (2004) found 6.5:1 (sexual:apomictic). All these studies were conducted with Paspalum notatum genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A single dominant ''locus'' is required for apomeiosis and parthenogenesis in the aposporous grasses Pennisetum/Cenchrus (Sherwood et al, 1994;OziasAkins et al, 1998), Brachiaria (Pessino et al, 1997), and Paspalum (Martinez et al, 2001) and in the diplosporous grass Tripsacum (Grimanelli et al, 1998). In all cases, penetrance of the trait varied among the apomictic siblings.…”
mentioning
confidence: 99%